Simple Skeletal Muscle Mass Estimation Formulas: What We Can Learn From Them - Heymsfield, Steven B.; Stanley, Abishek; Pietrobelli, Angelo; Heo, Moonseong (Frontiers in Endocrinology, 2020)
One century ago Harris and Benedict published a short report critically examining the relations 17 between body size, body shape, age, and basal metabolic rate. At the time, basal metabolic rate was a 18 vital measurement in diagnosing diseases such as hypothyroidism. Their conclusions and basal 19 metabolic rate prediction formulas still resonate today. Using the Harris-Benedict approach as a 20 template, we systematically examined the relations between body size, body shape, age, and skeletal 21 muscle mass (SM), the main anatomic feature of sarcopenia. The sample consisted of 12,330 non-22 Hispanic (NH) white and NH black participants in the US National Health and Nutrition Survey who 23 had complete weight, height, waist circumference, age, and dual-energy X-ray (DXA) absorptiometry 24 data. A conversion formula was used to derive SM from DXA-measured appendicular lean soft tissue 25 mass. Weight, height, waist circumference, and age alone and in combination were significantly 26 correlated with SM (all, p<0.001). Advancing analyses through the aforementioned sequence of 27 predictor variables allowed us to establish how at the anatomic level these body size, body shape, and 28 age measures relate to SM much in the same way the Harris-Benedict equations provide insights into 29 the structural origins of basal heat production. Our composite series of SM prediction equations 30 should prove useful in modeling efforts and in generating hypotheses aimed at understanding how 31 SM relates to body size and shape across the adult lifespan.